2023
DOI: 10.4274/tjo.galenos.2022.02489
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Vascularity Index and Choroidal Thickness Changes Following Renal Transplantation

Abstract: Objectives: This study aimed to evaluate changes in subfoveal choroidal thickness (SFCT), choroidal vascularity index (CVI), estimated glomerular filtration rate (GFR), mean arterial pressure (MAP), and intraocular pressure (IOP) after renal transplantation. Materials and Methods: A total of 49 renal transplantation patients were included in this prospective study. CVI and SFCT on enhanced-depth imaging optic coherence tomography (EDI-OCT), MAP at the cubital fossa, GFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Figure 1 schematically illustrates layers of the retina and the choroid (7). Clinical studies have shown that both the stromal and vascular structures of the choroid are impacted by various systemic diseases (8,9,10,11). New imaging methods that measure choroidal thickness (ChT) and choroidal vascularity index (CVI) have spurred research on the correlation between the choroid and numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 schematically illustrates layers of the retina and the choroid (7). Clinical studies have shown that both the stromal and vascular structures of the choroid are impacted by various systemic diseases (8,9,10,11). New imaging methods that measure choroidal thickness (ChT) and choroidal vascularity index (CVI) have spurred research on the correlation between the choroid and numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 schematically illustrates layers of the retina and the choroid. 7 Clinical studies have shown that both the stromal and vascular structures of the choroid are impacted by various systemic diseases [8][9][10][11]. New imaging methods that measure choroidal thickness (ChT) and choroidal vascularity index (CVI) have spurred research on the correlation between the choroid and numerous diseases.…”
Section: Introductionmentioning
confidence: 99%